ANALISIS KESALAHAN MAHASISWA MENYELESAIKAN SOAL KETAKSAMAAN YANG MELIBATKAN NILAI MUTLAK BERDASARKAN TEORI KASTOLAN - Fhela Vhantoria (Universitas Muhammadiyah Kotabumi, 2022)
Inequality involving absolute values ​​is an important course material because it is not only studied by mathematics education students but also by mechanical engineering students. In the process of solving inequalities, an absolute value is very reasonable when various errors occur. One theory of error is Kastolan. The identity of Kastolan's theory of errors is in the form of procedural, conceptual, and technical errors. The general purpose of this study was to determine student errors in solving inequalities involving absolute values ​​based on Kastolan's theory of errors and the form of the errors. This research method uses a qualitative research approach with the type of case study. The instruments in this study were: the main instrument and the supporting instrument. The data analysis technique used an interactive analysis model by Milles and Huberman. The conclusion of this study is the student's error in solving inequality problems involving absolute values ​​based on the Kastolan error theory and the form of the error. Conceptual errors in the form of errors in working without using theorems, laws, or formulas, errors in applying formulas, and incorrect problem-solving errors (having errors in determining the sign of inequality, errors in determining the intersection of two inequality conditions, and errors in drawing conclusions or Sets of completion). In addition, the type of technical error with the form of error is a counting error